Enhanced tunneling electroresistance in Pt/PZT/LSMO ferroelectric tunnel junctions in presence of magnetic field. Issue 174 (1st September 2016) - Barrionuevo, D.; Zhang, Le; Ortega, N.; Sokolov, A.; Kumar, A.; Scott, J. F.; Katiyar, R. S.
ABSTRACT: We report an enhancement of tunneling electroresistance (TER) in the presence of magnetic field for 7-nm PbZr0.52 Ti0.48 O3 (PZT) ferroelectric tunnel barriers sandwiched between platinum metal (Pt) and ferromagnetic La0.67 Sr0.33 MnO3 (LSMO) layers. The significant variation in TER was observed when Pt/PZT/LSMO junction was exposed to magnetic field and its values at zero bias changed from 57 (at 0 G) to 110 under 10 kG of magnetic field. We attributed this enhancement to change in resistance near the PZT/LSMO interface under magnetic field. Ferroelectric polarization reversal and application of magnetic field changed lattice strain, chemical bonding and charge modulation near PZT/LSMO interface which in turn affects the charge carrier density and transmission probability. Our results suggest the possibility to manipulate TER by magnetic field in ferroelectric tunnel junctions. These results should lead to performance improvement in the devices based on nano-scale ferroelectrics in quantum nanostructures, with application to low energy memories and logic devices.